К динамике горного оледенения Урала в условиях глобального потепления - Ворончихина, Евгения Александровна; Мышлявцева, Светлана Эдуардовна; Дылдин, Игорь Юрьевич; Челышев, Сергей Рафхатович (Географический вестник=Geographical bulletin, 2017)
нет аннотации